2015
DOI: 10.1016/j.jhsa.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pediatric Brachial Plexus Injury on Families

Abstract: Purpose To determine the impact on families of children with brachial plexus injuries in order to best meet their clinical and social needs. Methods Our cross-sectional study included families with children between the ages of 1 and 18 with birth or non-neonatal brachial plexus injuries (BPI). The consenting parent or guardian completed a demographic questionnaire and the validated Impact on Family Scale during a single assessment. Total scores can range from 0-100, with the higher the score indicating a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Family caregiver groups were composed of 90% parents (74% mothers), and 9% were other family members (eg, grandparent). The sample composition was similar to other studies examining caregivers/parents of children with impairment [10,29]. Sixteen percent of the caregivers had a high school education (84% had at least some college and/or a college or graduate degree), and 42% had family income $75,000 and greater.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Family caregiver groups were composed of 90% parents (74% mothers), and 9% were other family members (eg, grandparent). The sample composition was similar to other studies examining caregivers/parents of children with impairment [10,29]. Sixteen percent of the caregivers had a high school education (84% had at least some college and/or a college or graduate degree), and 42% had family income $75,000 and greater.…”
Section: Resultsmentioning
confidence: 61%
“…Time commitment and financial burdens from constant clinic visits, therapy sessions, or even surgical interventions could cause stress to caregivers. Previous studies investigating the impact of NBPP on parents and/or families showed that this condition not only affected children's HRQOL, but also influenced the whole family [29,30,37,38]. An interdisciplinary clinic with social work services could provide comprehensive support and resources for patients, families, and schools to help reduce the impact of social difficulties while treating children with NBPP.…”
Section: Discussionmentioning
confidence: 99%
“…External factors including physical functioning or visible impairment might be more evident and lead to greater agreement between children and parents, whereas internal factors such as emotional, body image, self‐esteem, and SDet are more difficult to perceive and evaluate [34]. In addition, the chronic condition of NBPP also might influence caregivers' psychosocial status and family functioning [35,36]. The financial burden and time commitment of clinic appointments might cause stress and disturbance of family routines [9,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Obstetric brachial plexus injuries (OBPIs) are rare [ 1 , 2 ] but can have significant implications for those affected [ 3 ], their caregivers [ 4 ] and the wider health system [ 5 ]. These injuries – sometimes referred to as Erb’s palsies – can occur as a result of the mismanagement of an obstetric emergency: shoulder dystocia; where the baby’s head is delivered but its anterior shoulder is impacted against the mother’s pelvic bone [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the only quality of life utility scores related to OBPIs have been assigned at a distance, by healthcare professionals from outside the specialties involved in OBPIs [ 11 ]. There has been no direct assessment of the impact of OBPIs on individuals and although there is a growing body of research investigating the effects of OBPIs on families and caregivers [ 4 , 12 , 13 ], it has never been expressed using utility scores.…”
Section: Introductionmentioning
confidence: 99%